Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Think Pair Share (TPS) Terhadap Motivasi Belajar Siswa Kelas VII SMP Negeri 2 Wangi-Wangi Selatan - Rahmatia Rahmatia; Lia Ihwana (Jurnal Akademik Pendidikan Matematika, 2021)
Objective of this in Think Pair Share toward student learning motivation at grade VII SMP NeGERI 2 Wangi-Wangi Selatan. This research was quantitative research with quasi experimental method. Populations in this research was all grade VII SMP Negeri 2 Wangi-Wangi Selatan consisted of 100 students. Sample in the research was taken by using random sampling technique which consisted of 50 students were 25 students for experimental class and 25 student for control class. Instrument used in this research was questionnaire. Research outcome obtained showed that based on the result of independent t-test, it found that t-count = 3.312 and the t-table score in the significance level of 0.05 (5%) was 2.011 with df 48. As the > , therefore the hypothesis was accepted. So that it can be concluded that cooperative learning in Thin Pair Share type (TPS) affected toward student learning motivation at grade VII SMP Negeri 2 Wangi-Wangi Selatan.